PENGARUH TINGKAT KESULITAN KEUANGAN TERHADAP KONSERVATIME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR - Tasum Tasum (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to obtain empirical evidence of the Effect of Financial Difficulty Levels, Debt Levels, Receivables and Company Size on Accounting Conservatism in Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesian Stock Exchange.The research method uses descriptive quantitative analysis.The results of this study indicate that (1) the level of financial distress has no effect on the occurrence of accounting conservatism. (2) the level of debt does not have a negative effect on the occurrence of accounting conservatism. (3) Receivables have no effect on the occurrence of Accounting Conservatism. (4) Company size does not have a negative effect on the occurrence of Accounting Conservatism.